Analisis Kondisi Peta Persebaran Pencahayaan dan Kebisingan di PT. Pamapersada Nusantara Distrik Baya Menggunakan Software Surfer - R, Andrian; Munir, Rahmawati; Putri, Devina; Wardani, Wardani; Mislan, Mislan (Universitas Islam Negeri Alauddin Makassar, 2024)
This research was motivated by the issues of lighting and noise in the mining company. Insufficient lighting could lead to accidents and eye strain, while noise from heavy machinery could cause health problems and reduce workers' performance. Therefore, this study aimed to identify and map areas with levels of lighting and noise at PT. Pamapersada Nusantara Distrik Baya, as well as to analyze the distribution map based on SNI 16-7062-2004 for lighting and SNI 8427:2017 for noise. The results of the study showed that there was a variation in lighting and noise levels in different areas, caused by factors such as light source obstructions like large parked units in the measured area and working hours. Areas with suboptimal lighting often hindered workers' tasks, while areas with high noise levels posed a risk of hearing loss. The conclusion of this study indicated that the variation in lighting and noise levels in the work areas of PT. Pamapersada Nusantara Distrik Baya was significantly influenced by environmental conditions during working hours. The recommendations provided by PT. Pamapersada Nusantara Distrik Baya to improve employee comfort and performance included the equalization and maintenance of lighting and noise infrastructure.